Liability of employers for third party harassment in the UK. Issue 1 (5th September 2020) - Middlemiss, Sam
Abstract : Purpose: This paper aims to summarise current law dealing with third party harassment in workplaces in the UK and make recommendations for improving law. Design/methodology/approach: Review of case law, articles etc. Findings: It is found that the current law is inadequate and unclear, and in dire need of reform. Research limitations/implications: This research study will be useful for trade unions and employers and employees and workers. Practical implications: This study supports the cause of reform of the law. Originality/value: To the best of the author's knowledge, this study is an original piece of work.